Composite electrolyte and power storage device
Patent Information
- Application Number
- CN202480042754.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-06-25
- Publication Date
- 2026-01-30
AI Technical Summary
Existing composite electrolytes of inorganic and organic solid electrolytes have low ion conductivity and poor performance, which cannot meet the needs of high-energy-density energy storage devices.
By combining specific inorganic solid electrolytes with organic solid electrolytes, and controlling the porosity of the composite electrolyte to below 15%, especially by using oxides and molecular crystals with NASICON-type crystal structures, and combining them with materials such as imide-based alkali metal salts, a composite electrolyte with high ion conductivity is formed.
A composite electrolyte with high ion conductivity has been developed, which improves the safety and ion conductivity of energy storage devices and is suitable for energy storage devices such as secondary batteries and capacitors.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] [Cross-reference to related applications] This application claims priority based on Japanese Patent Application No. 2023-108816, filed on June 30, 2023, the entirety of which is incorporated herein by reference.
[0002] This disclosure relates to composite electrolytes and energy storage devices. Background Technology
[0003] As energy storage devices, various rechargeable batteries, such as nickel-metal hydride batteries and lithium-ion batteries, as well as double-layer capacitors, have been put into practical use. Among them, lithium-ion batteries are widely used due to their high energy density and high battery capacity. In addition, in recent years, sodium-ion batteries, potassium-ion batteries, and magnesium-ion batteries, which use lithium as a substitute for lithium, a rare metal, have attracted attention as alternatives to lithium-ion batteries.
[0004] Lithium-ion secondary batteries, widely used as energy storage devices, have a negative electrode, a positive electrode, and an electrolyte. They are charged and discharged by allowing lithium ions to move between the two electrodes via the electrolyte. Previously, organic electrolytes were primarily used. However, in recent years, to eliminate concerns about internal short circuits caused by electrolyte leakage, overcharging, and over-discharging, technologies have been proposed to use solid or gel-like electrolytes made of inorganic or organic materials instead of organic electrolytes.
[0005] Inorganic solid electrolytes exhibit excellent ionic conductivity; however, due to their powder form, their formability during electrolyte layer fabrication is not ideal. Furthermore, achieving excellent ionic conductivity using inorganic solid electrolytes requires sintering at high temperatures (e.g., exceeding 1000°C) for oxide-based solid electrolytes and high-pressure pressing at high pressures (e.g., exceeding 10 MPa) for sulfide-based solid electrolytes, resulting in significant process limitations. Organic solid electrolytes offer moderate flexibility and high formability; however, compared to inorganic solid electrolytes, they tend to have lower ionic conductivity.
[0006] Therefore, in recent years, in order to develop novel solid electrolytes with excellent performance, research has been conducted on obtaining composite electrolytes formed from inorganic solid electrolytes and organic solid electrolytes (for example, see Patent Document 1). Patent Document 1 discloses a composite electrolyte using lithium lanthanum zirconium oxide as the inorganic solid electrolyte and using polyethylene oxide containing lithium salt as the organic solid electrolyte.
[0007] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2022-160569 Summary of the Invention
[0008] The technical problem that the invention aims to solve After conducting research, the inventors discovered that conventional composite electrolytes formed using inorganic and organic solid electrolytes have low ionic conductivity and poor performance. From the perspective of further improving the quality of energy storage devices, there is a need to develop composite electrolytes with even higher ionic conductivity.
[0009] This disclosure was made in view of the following circumstances, one of the objects of which is to provide a composite electrolyte that exhibits high ion conductivity in a composite electrolyte of inorganic solid electrolyte and organic solid electrolyte.
[0010] Technical solutions for solving technical problems In order to solve the above-mentioned technical problems, the inventors conducted in-depth research and discovered that, in composite electrolytes of inorganic solid electrolytes and organic solid electrolytes, by using a specific substance as the organic solid electrolyte and focusing on porosity, a solid electrolyte exhibiting high ion conductivity can be obtained. According to this disclosure, the following composite electrolyte and energy storage device are provided.
[0011] [1] A composite electrolyte comprising an inorganic solid electrolyte and an organic solid electrolyte, wherein the organic solid electrolyte comprises molecular crystals and the porosity of the composite electrolyte is less than 15%.
[0012] [2] According to the composite electrolyte of [1], wherein the inorganic solid electrolyte comprises an oxide having a NASICON-type crystal structure.
[0013] [3] According to the composite electrolyte of [2], wherein the oxide having a NASICON-type crystal structure comprises the general formula: Li 1+x+y-z M1 x Zr 2-x M2 y M3 z P 3-y-z O 12 The solid electrolyte shown is (where M1 contains Fe, In or Al, M2 contains Si, M3 contains W, and satisfies x > 0, y ≥ 0, z ≥ 0 and y + z > 0).
[0014] [4] According to the composite electrolyte of [2], wherein the oxide having a NASICON-type crystal structure comprises the general formula: Na 3+2x+y+α M4 x M5 y M6 z Zr 2-x-y-z Si2+α P 1-α O 12 The solid electrolyte shown (where M4 contains elements that become divalent cations, M5 contains Al and may contain elements other than Al that become trivalent cations, M6 contains Ti and may contain elements other than Ti, Zr and Si that become tetravalent cations, satisfying x≥0, y≥0, z≥0 and x+y+z>0, and satisfying α>0).
[0015] [5] The composite electrolyte according to any one of [1] to [4], wherein the molecular crystal comprises organic molecules and alkali metal salts as constituent units.
[0016] [6] According to the composite electrolyte of [5], the number of carbon atoms in each molecule of the organic molecule is 6 or less.
[0017] [7] The composite electrolyte according to [5] or [6], wherein the alkali metal salt comprises an imide-based alkali metal salt.
[0018] [8] The composite electrolyte according to any one of [5] to [7], wherein the organic molecule has at least one atom selected from sulfur, oxygen, nitrogen and phosphorus.
[0019] [9] The composite electrolyte according to any one of [5] to [8], wherein the organic molecule is selected from at least one of sulfone and nitrile.
[0020]
[10] An energy storage device comprising any one of [1] to [9] a composite electrolyte.
[0021] Invention Effects According to this disclosure, a composite electrolyte exhibiting high ionic conductivity in a composite electrolyte of inorganic solid electrolyte and organic solid electrolyte can be obtained. Furthermore, by using this composite electrolyte as the electrolyte layer in energy storage devices such as secondary batteries and capacitors, energy storage devices can achieve a balanced combination of safety assurance resulting from the solidification of the electrolyte layer and high ionic conductivity. Attached Figure Description
[0022] Figure 1 This is a simplified diagram of the molding die used in the preparation of sample particles. Detailed Implementation
[0023] The following provides a detailed description of the composite electrolyte of this disclosure and the energy storage device manufactured using the composite electrolyte.
[0024] Complex Electrolytes The composite electrolyte disclosed herein contains an inorganic solid electrolyte (hereinafter also referred to as "(X) component") and a molecular crystal as an organic solid electrolyte (hereinafter also referred to as "(Y) component"). Furthermore, the porosity of the composite electrolyte disclosed herein is 15% or less.
[0025] If the porosity of the composite electrolyte exceeds 15%, the ionic conductivity of the composite electrolyte will be low, resulting in poor practicality. From the viewpoint of obtaining a composite electrolyte with excellent ionic conductivity, the porosity of the composite electrolyte is preferably 12% or less, more preferably 10% or less, and even more preferably 8% or less. There is no particular limitation on the lower limit of the porosity of the composite electrolyte; it is acceptable to have a porosity of 0% or more.
[0026] It should be noted that in this specification, the porosity of the composite electrolyte is defined as φ (unit: %) and the density of the composite electrolyte is defined as D (unit: g·cm³). -3 The theoretical density of the composite electrolyte is set as D′ (unit: g·cm³). -3 In the case of ), the porosity of the composite electrolyte is expressed by the following mathematical formula.
[0027] φ = (1 - D / D′) × 100 The density (D) of the composite electrolyte used in the porosity calculation can be used in conjunction with the mass of the composite electrolyte (M, in g) and the contact area between the composite electrolyte and the electrode (S, in cm²). 2 The thickness (L, unit: cm) of the composite electrolyte is expressed by the following mathematical formula.
[0028] D = M / (S × L) Furthermore, the theoretical density (D′) is calculated by summing the values obtained by multiplying the densities of components (X) and (Y) in the composite electrolyte by the mass ratio of each component. Details of the calculation methods for porosity and density (D) are as described in the embodiments described later. It should be noted that the porosity of the composite electrolyte can be adjusted, for example, by adjusting the temperature of the heat treatment after mixing components (X) and (Y).
[0029] Next, the components constituting the composite electrolyte of this disclosure will be described in detail.
[0030] <(X) Component: Inorganic solid electrolyte> In the composite electrolyte disclosed herein, the inorganic solid electrolyte included as component (X) is not particularly limited as long as it is an inorganic solid exhibiting ion conductivity. For example, oxide-based solid electrolytes, sulfide-based solid electrolytes, and chloride-based solid electrolytes can be used as component (X). Regarding component (X), from the perspective of high ion conductivity, oxide-based solid electrolytes or sulfide-based solid electrolytes are preferred; from the perspective of high atmospheric safety, oxide-based solid electrolytes are more preferred.
[0031] There are no particular limitations on the crystal structure of component (X). Examples of crystal structures that can be considered as component (X) include the NASICON type structure, LISICON type structure, perovskite type structure, and garnet type structure.
[0032] As a specific example of component (X), a solid electrolyte having a NASICON-type structure can be cited as: Li 1+ x Al x Ti 2-x (PO4)3 (x≥0, also known as "LTP" or "LATP"), Li 1+x Al x Ge 2-x (PO4)3 (x≥0, also known as "LGP" or "LAGP"), LiZr2(PO4)3 (also known as "LZP"), and Na3Zr2Si2PO as NASICON 12 (Also known as "NZSP"), oxides obtained by replacing a portion of the elements constituting these compounds with various elements (such as B, Na, Al, Si, Ca, Ga, Ge, Sc, Fe, Sr, In, Ti, Hf, Sn, V, Nb, Ta, Sb, Bi, W and lanthanides, etc.).
[0033] As a solid electrolyte with a LISICON-type structure, Li can be cited as an example. 14 ZnGe4O 16 Oxides obtained by replacing a portion of the elements constituting the compound with the aforementioned elements.
[0034] Li can be cited as an example of a solid electrolyte with a perovskite-type structure. 0.35 La 0.55 TiO3, oxides obtained by replacing some of the elements constituting the compound with the aforementioned elements, etc.
[0035] Li7La3Zr2O is an example of a solid electrolyte with a garnet-type structure. 12 and Li5La3Nb2O 12Oxides obtained by replacing some of the elements constituting these compounds with the aforementioned elements.
[0036] One aspect of the composite electrolyte disclosed herein is an organic-inorganic mixed solid electrolyte comprising an inorganic solid electrolyte having a NASICON-type crystal structure and a molecular crystal as an organic solid electrolyte. The NASICON-type crystal structure differs from layered structures, etc., allowing for a wide three-dimensional movement space for alkali metal ions, and zirconium (Zr) is stable even at high voltages, thus making it useful as a solid electrolyte for high operating voltages. In the composite electrolyte of this disclosure, an oxide having a NASICON-type crystal structure is preferably used as the inorganic solid electrolyte (X) component. It should be noted that the crystal structure of the solid electrolyte can be determined by the diffraction pattern obtained by powder X-ray diffraction (XRD).
[0037] When using an oxide having a NASICON-type crystal structure as the (X) component, preferred examples of such oxides include oxide (y1) and oxide (y2) as shown below.
[0038] Oxide (y1): General formula Li 1+x+y-z M1 x Zr 2-x M2 y M3 z P 3-y-z O 12 The solid electrolyte shown (where M1 contains Fe, In or Al, M2 contains Si, M3 contains W, and satisfies x > 0, y ≥ 0, z ≥ 0 and y + z > 0) Oxides (y2): General formula: Na 3+2x+y+α M4 x M5 y M6 z Zr 2-x-y-z Si 2+α P 1-α O 12 The solid electrolyte shown (where M4 contains elements that become divalent cations, M5 contains Al and may contain elements other than Al that become trivalent cations, M6 contains Ti and may contain elements other than Ti, Zr and Si that become tetravalent cations, satisfying x≥0, y≥0, z≥0 and x+y+z>0, and satisfying α>0) Regarding oxides (y1) Oxide (y1) is a solid electrolyte in which a portion of Zr is replaced by M1 (containing Fe, In or Al) and a portion of P is replaced by M2 (containing Si) and / or M3 (containing W) in an oxide with LiZr2(PO4)3 as the basic framework.
[0039] In the oxide (y1), M1 only needs to contain Fe or In. That is, M1 can be Fe, In, or Al, or it can contain elements other than Fe, In, or Al that can become trivalent cations. Examples of elements other than Fe, In, or Al that can become trivalent cations include elements from Group 13, transition elements (Groups 3-11), Sb, Bi, etc.
[0040] M2 only needs to contain Si. That is, M2 can be Si, or it can further contain elements other than Si that can become tetravalent cations. Examples of elements other than Si that can become tetravalent cations include elements in Group 14 other than Si, transition elements (Groups 3 to 11) that can become tetravalent cations, Te, etc.
[0041] M3 only needs to contain W. That is, M3 can be W, or it can further contain elements other than W that can become hexavalent cations. Examples of elements other than W that can become hexavalent cations include transition elements (groups 3 to 11) and group 16 elements.
[0042] In the general formula for oxide (y1), x, y, and z are not particularly restricted as long as x > 0, y ≥ 0, z ≥ 0, and y + z > 0. For example, in the case of x > 0, y > 0, and z = 0, oxide (y1) is derived from "Li 1+x+y M1 x Zr 2-x M2 y P 3-y O 12 " indicates. In the case of x > 0, y = 0, and z > 0, the oxide (y1) is represented by "Li 1+x-z M1 x Zr 2-x M3 z P 3-z O 12 " indicates. In the case of x > 0, y > 0, and z > 0, the oxide (y1) is represented by "Li 1+x+y-z M1 x Zr 2-x M2 y M3 z P 3-y-z O 12 "express.
[0043] Regarding x, y, and z in the general formula for oxide (y1), more specifically, from the viewpoint of not easily forming impurity phases and thus obtaining a solid electrolyte exhibiting high ionic conductivity, it is preferable that x ≤ 0.3, more preferably that x ≤ 0.25. Regarding the lower limit of x, it is preferable that x ≥ 0.01, more preferably that x ≥ 0.05, and even more preferably that x ≥ 0.10.
[0044] Regarding y, considering that it preferentially acts on the formation of the α phase, thereby obtaining a solid electrolyte with higher ionic conductivity, it is preferable that y ≤ 0.2, more preferably that y ≤ 0.15, and even more preferably that y ≤ 0.10. Furthermore, when y > 0, regarding the lower limit of y, it is preferable that y ≥ 0.01, more preferably that y ≥ 0.03. It should be noted that zirconium phosphate oxides with a NASICON-type crystal structure can take α, α′, β, and β′ phases as their phase structures. Among these, the α phase has an isotropic crystal structure, thus exhibiting the highest Li ion conductivity.
[0045] Regarding z, from the perspective of suppressing the formation of impurity phases and obtaining solid electrolytes exhibiting higher ionic conductivity, it is preferable that z ≤ 0.2, more preferably that z ≤ 0.15, and even more preferably that z ≤ 0.10. When z > 0, regarding the lower limit of z, it is preferable that z ≥ 0.01, and more preferably that z ≥ 0.03.
[0046] Regarding oxides (y2) The oxide (y2) is formed in the form of Na3Zr2Si2PO4 12 A solid electrolyte in which a portion of Zr in an oxide with a basic framework is replaced by at least one of M4 (containing elements that become divalent cations), M5 (containing Al), and M6 (containing Ti), and the composition contains more Si than the basic framework.
[0047] In oxides (y2), as M4, examples include elements from Group 2, Group 12, transition elements (Groups 3-11) that can become divalent cations, Sn, Pd, etc.
[0048] M5 only needs to contain Al. That is, M5 can be Al, or it can further contain elements other than Al that can become trivalent cations. Examples of elements other than Al that can become trivalent cations include Group 3 elements, Group 13 elements other than Al, transition elements (Groups 3-11) that can become trivalent cations, Sb, Bi, etc. Among Group 13 elements other than Al, B (boron) is preferred.
[0049] M6 only needs to contain Ti. That is, M6 can be Ti, or it can further contain elements other than Ti, Zr, and Si that can become tetravalent cations. Examples of elements other than Ti, Zr, and Si that can become tetravalent cations include elements in Group 14 other than Si, and transition elements (Groups 3 to 11 other than Ti and Zr) that can become tetravalent cations (Te, Ce, Th).
[0050] In the general formula for oxide (y2), x, y, and z satisfy x≥0, y≥0, z≥0, and x+y+z>0, while α is not specifically limited as long as α>0. For example, in the case of x=0, y>0, and z>0, oxide (y2) is derived from "Na 3+y+α M5 y M6 z Zr 2-y- z Si 2+α P 1-α O 12 "Indicates that when y = 0, x > 0, and z > 0, the oxide (y2) is represented by "Na 3+2x+α M4 x M6 z Zr 2-x-z Si 2+α P 1-α O 12 "Indicates that when z = 0, x > 0, and y > 0, the oxide (y2) is represented by "Na 3+2x+y+α M4 x M5 y Zr 2-x-y Si 2+α P 1-α O 12 "Indicates that when x = 0, y = 0 and z > 0, the oxide (y2) is represented by "Na 3+α M6 z Zr 2-z Si 2+α P 1-α O 12 "express.
[0051] Regarding x, y, z, and α in the general formula for oxide (y2), more specifically, from the viewpoint of not easily forming impurity phases and thus obtaining a solid electrolyte exhibiting high ionic conductivity, it is preferable that x ≤ 0.3, more preferably x ≤ 0.2, and even more preferably x ≤ 0.1. When x > 0, regarding the lower limit of x, it is preferable that x ≥ 0.01, more preferably x ≥ 0.03, and even more preferably x ≥ 0.05.
[0052] Regarding y, from the perspective of suppressing the formation of impurity phases and thereby obtaining a solid electrolyte with higher ionic conductivity, it is preferable that y ≤ 0.3, more preferably that y ≤ 0.2, and even more preferably that y ≤ 0.1. Furthermore, when y > 0, regarding the lower limit of y, it is preferable that y ≥ 0.01, more preferably that y ≥ 0.03, and even more preferably that y ≥ 0.05.
[0053] Regarding z, from the perspective of suppressing the formation of impurity phases and obtaining solid electrolytes that can exhibit higher ionic conductivity, it is preferable that z ≤ 0.3, more preferably that z ≤ 0.2, and even more preferably that z ≤ 0.1. When z > 0, regarding the lower limit of z, it is preferable that z ≥ 0.01, more preferably that z ≥ 0.03, and even more preferably that z ≥ 0.05.
[0054] Regarding α, considering that a higher Si substitution amount reduces ionic conductivity, it is preferable that α ≤ 1.0, more preferably α ≤ 0.9, even more preferably α ≤ 0.8, even more preferably α ≤ 0.7, even more preferably α ≤ 0.6, and even more preferably α ≤ 0.5. Furthermore, regarding the lower limit of α, it is preferable that α ≥ 0.15, more preferably α ≥ 0.25, and even more preferably α ≥ 0.3.
[0055] It should be noted that in the above general formulas representing oxides (y1) and oxides (y2), the stoichiometry of O is denoted as 12. However, as long as the overall electroneutrality of the oxide is maintained, the stoichiometry of O does not have to be strictly 12. That is, the O in oxide (y1) can be a value less than 12 or greater than 12, as long as the overall electroneutrality of oxide (y1) is maintained. Regarding oxide (y1), for example, for Li... 1+x+y-z M1 x Zr 2-x M2 y M3 z P 3-y-z O 12±β The compounds shown (where 0 ≤ β ≤ 1, and M1, M2, M3, x, y, and z are the same as M1, M2, M3, x, y, and z in the formula above as the general formula for oxides (y1)) are also included in oxide (y1) as long as they maintain the electroneutrality of oxide (y1) as a whole. Similarly, the O in oxide (y2) can be a value less than 12 or greater than 12, as long as it maintains the electroneutrality of oxide (y2) as a whole. For example, for Na… 3+2x+y+α M4 x M5 y M6 z Zr 2-x-y-z Si 2+α P1-α O 12+γ The compound shown (where 0≤γ≤1, and M4, M5, M6, x, y, z and α are the same as M4, M5, M6, x, y, z and α in the above formula as the general formula of oxide (y2)) is also included in oxide (y2) as long as the electroneutrality of oxide (y2) as a whole is maintained.
[0056] There are no particular limitations on the manufacturing methods of oxides (y1) and oxides (y2). Oxides (y1) and oxides (y2) can be manufactured, for example, by weighing and mixing raw materials in a manner that satisfies the stoichiometric ratios of the compositions shown in the above general formulas (mixing process), and then firing the resulting mixture (firing process).
[0057] As raw materials for oxide (y1), supply components corresponding to the elements used to obtain the target oxide (y1) can be used, including Li supply component, M1 supply component (Fe supply component, In supply component, or Al supply component), M2 supply component (Si supply component), M3 supply component (W supply component), Zr supply component, and P supply component. For example, in the case of obtaining an oxide (y1) where y > 0 and z = 0, Li supply component, M1 supply component, M2 supply component, Zr supply component, and P supply component can be used as raw materials.
[0058] As the Li supply component, M1 supply component (Fe supply component, In supply component, or Al supply component), M2 supply component, M3 supply component, Zr supply component, and P supply component for obtaining oxide (y1), for example, carbonates, bicarbonates, sulfates, sulfites, nitrates, nitrites, phosphates, acetates, citrates, ammonium salts, oxides, hydroxides, chlorides, sulfides, etc., that can use these metal elements. It should be noted that for these supply components, one supply component can be a compound containing two or more elements selected from Li, M1, M2, M3, Zr, and P.
[0059] As the P supply component, compounds containing one or more elements selected from Li, M1, M2, M3, and Zr are preferred. Among these, zirconium phosphate compounds are preferred as the supply component (the supply component for both Zr and P). Examples of zirconium phosphate compounds include zirconium hydrogen phosphate such as Zr(HPO4)2 and Zr(HPO4)2·nH2O; zirconium phosphate such as Zr3(PO4)4; zirconium hydrogen phosphate such as Zr(PO4)(H2PO4) and Zr(PO4)(H2PO4)2·nH2O (n is 0 ≤ n ≤ 2); in addition, examples include HZr2(PO4)3, ZrP2O7, and (ZrO)2P2O7. From the perspective of good handling of the inorganic solid electrolyte during manufacturing, Zr(HPO4)2·nH2O, also known as layered zirconium phosphate, is preferred.
[0060] As a raw material for oxide (y2), a supply component corresponding to the element used to obtain the target oxide (y2) can be used, including Na, M4, M5, M6, Zr, Si, and P. For example, in the case of obtaining an oxide (y2) where x = 0 and y = 0, Na, M6, Zr, Si, and P are used as raw materials. It should be noted that, for these supply components, one of the supply components can be a compound containing two or more elements selected from Na, M4, M5, M6, Zr, Si, and P.
[0061] As raw materials for oxides (y2), namely Na supply components, M4 supply components, M5 supply components, M6 supply components, Zr supply components, Si supply components, and P supply components, carbonates, bicarbonates, sulfates, sulfites, nitrates, nitrites, phosphates, acetates, citrates, ammonium salts, oxides, hydroxides, chlorides, sulfides, etc., of these metal elements can be utilized. It should be noted that, for these supply components, one supply component can be a compound containing two or more elements selected from Na, M4, M5, M6, Zr, Si, and P. As a P supply component, zirconium phosphate compounds are preferably used, among which layered zirconium phosphate is preferred.
[0062] When manufacturing oxides (y1) and (y2), the raw materials can be mixed by dry mixing, but it is preferable to use wet mixing with a liquid. By using wet mixing, compared with dry mixing, the density of the sinter obtained through the firing process can be increased, and the ionic conductivity of the resulting solid electrolyte can also be relatively improved. As the liquid used in wet mixing, water, various organic solvents, and mixtures thereof can be appropriately used.
[0063] In the firing process, firing can be performed without shaping the mixture obtained in the mixing process, or it can be performed after shaping. The firing temperature is not limited; for example, it can be set to 900°C or higher, preferably 1000°C or higher, more preferably 1150°C or higher, and even more preferably 1200°C or higher. Regarding the upper limit of the firing temperature, for example, it can be set to 1500°C or lower, preferably 1400°C or lower, and more preferably 1350°C or lower. During firing, the temperature can also be gradually increased from a temperature lower than the firing temperature (pre-firing) and then maintained at the temperature required for final firing.
[0064] When pre-firing is performed, the pre-fired material can be pulverized before the subsequent firing process. When firing in multiple temperature zones, for example, the firing process can be divided into three stages: a first pre-firing at a temperature zone above 100°C and below 800°C, a second pre-firing at a temperature zone above 800°C and below 1200°C, and a final firing at a temperature zone above 1200°C. The pre-fired material is pulverized each time the firing temperature zone is changed. There is no limit to the firing time; for example, the pre-firing can be set to 1 hour or more and 40 hours or less, and the final firing can be set to 1 hour or more and 40 hours or less.
[0065] It should be noted that oxide (y1) exhibits high Li-ion conductivity, while oxide (y2) exhibits high Na-ion conductivity. Therefore, oxide (y1) is suitable as a material for composite electrolytes used in energy storage devices where the charge carrier is lithium ion. Additionally, oxide (y2) is suitable as a material for composite electrolytes used in energy storage devices where the charge carrier is sodium ion.
[0066] The inorganic solid electrolyte obtained through the calcination process is preferably pulverized in powder form using any method for the manufacture of composite electrolytes. Pulverization of the inorganic solid electrolyte can be performed using, for example, ball mills, bead mills, mixers, or other pulverizers.
[0067] For the average particle size of the inorganic solid electrolyte used in the manufacture of composite electrolytes, the particle size measured in an aqueous medium is preferably 0.1 mm as the median particle size on a volume basis. m m or more and 20 m Below μm. When the average particle size of the inorganic solid electrolyte is within the above-mentioned range, a composite electrolyte with better processability and high ionic conductivity can be obtained, and is therefore preferred. From the viewpoint of processability, the average particle size of the inorganic solid electrolyte, calculated as the median particle size on a volume basis, is more preferably 0.2 μm. m m or more, and more preferably 0.3 mμm or larger. Furthermore, from the viewpoint of further improving ionic conductivity, the average particle size of the inorganic solid electrolyte, measured as the median particle size on a volume basis, is more preferably 15 μm or larger. m m or less, more preferably 10 m Below μm. It should be noted that the average particle size of the inorganic solid electrolyte is based on laser diffraction / scattering particle size determination. For details regarding the determination method, please refer to the methods described in the examples below.
[0068] From the viewpoint of obtaining a composite electrolyte with high ionic conductivity by utilizing the properties of inorganic solid electrolytes, the content of inorganic solid electrolyte in the composite electrolyte relative to the total amount of the composite electrolyte is preferably 1% by volume or more, more preferably 2% by volume or more, further preferably 5% by volume or more, and even more preferably 10% by volume or more. Furthermore, regarding the upper limit of the content of inorganic solid electrolyte, considering the need to sufficiently reduce the interfacial resistance of the inorganic solid electrolyte particles, thereby improving ionic conductivity, relative to the total amount of the composite electrolyte, it is preferably 99% by volume or less, more preferably 95% by volume or less, further preferably 85% by volume or less, even more preferably 75% by volume or less, even more preferably 70% by volume or less, and even more preferably 65% by volume or less. One type of inorganic solid electrolyte can be used alone, or two or more types can be used in combination.
[0069] <(Y) Composition: Molecular crystal> In the composite electrolyte of this disclosure, the molecular crystal included as component (Y) is a solid in which the constituent units are regularly arranged in a crystal lattice. As component (Y), an organic solid electrolyte comprising organic molecules and alkali metal salts as constituent units is preferably used. In particular, as component (Y), an organic solid electrolyte comprising an organic molecule (hereinafter also referred to as "(A) organic molecule") having at least one atom selected from sulfur, oxygen, nitrogen, and phosphorus atoms and an alkali metal salt as constituent units is preferably used. The molecular crystal comprising (A) organic molecules and alkali metal salts exhibits excellent ion conductivity due to the regular arrangement of the (A) organic molecules and alkali metal salts as constituent units, thus making it suitable.
[0070] (A) Organic molecules (A) The number of at least one atom selected from sulfur, oxygen, nitrogen, and phosphorus atoms in an organic molecule is not particularly limited. (A) In an organic molecule, the number of at least one atom selected from sulfur, oxygen, nitrogen, and phosphorus atoms per molecule is preferably 1 to 8, more preferably 2 to 6. Among these, (A) the organic molecule preferably has 2 or more atoms selected from sulfur, oxygen, and nitrogen atoms per molecule, more preferably 2 to 6.
[0071] (A) The molecular weight of the organic molecule is, for example, 300 or less, preferably 250 or less, and more preferably 200 or less. Regarding the lower limit of the molecular weight of the (A) organic molecule, it is, for example, 20 or more, preferably 40 or more, and more preferably 50 or more. Furthermore, from the viewpoint of promoting the crystallization of the mixture of (A) organic molecule and alkali metal salt, the total number of carbon atoms per molecule of (A) organic molecule is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less. Additionally, the total number of carbon atoms per molecule of (A) organic molecule is preferably 2 or more.
[0072] As specific examples of (A) organic molecules, organic molecules having sulfur atoms include sulfones, thioethers, thiols, thioesters, thiocarbonates, sulfoxides, and sulfonamides.
[0073] Examples of organic molecules containing nitrogen atoms include nitriles, amines, and amides.
[0074] Examples of organic molecules containing phosphorus atoms include phosphine, phosphine oxide, and phosphine imine.
[0075] As organic molecules containing oxygen atoms, examples include organic molecules containing sulfur atoms, organic molecules containing nitrogen atoms, and organic molecules containing phosphorus atoms, as well as ethers, esters, ketones, and carbonates. It should be noted that the (A) organic molecule constituting the molecular crystal can be a single type or two or more types.
[0076] From the perspective of further improving the ionic conductivity of the molecular crystal, (A) the organic molecule is preferably selected from at least one of the following: organic molecules having sulfur and oxygen atoms, organic molecules having nitrogen atoms, and organic molecules having phosphorus atoms.
[0077] (Organic molecules containing sulfur and oxygen atoms) Sulfones are preferred as organic molecules having sulfur and oxygen atoms. A preferred example of a sulfone is the molecule shown in the following formula (1).
[0078] [Chemistry 1]
[0079] (In equation (1), R) 1 and R 2 Each is independently alkyl or alkoxy, or represents R. 1 With R 2 The ring structure formed by bonding, wherein the total number of carbon atoms in formula (1) is 2 to 16. The molecule shown in formula (1) above (hereinafter also referred to as "(A-1) molecule") is a chain or cyclic molecule having a sulfonyl group (-SO2-). In formula (1) above, R... 1 and R 2 In the case of alkyl or alkoxy groups, the alkyl and alkoxy groups can be straight-chain or branched. Additionally, the number of carbon atoms in each alkyl and alkoxy group (i.e., R...) 1 and R 2 The number of carbon atoms in each group) as long as R 1 and R 2 The total number of carbon atoms is 2 to 16, without any particular limitation. In the manufacture of molecular crystals, from the viewpoint of crystallizing a mixture of the (A-1) molecule's supply component and an alkali metal salt, R... 1 and R 2 The number of carbon atoms in each is preferably 1 to 3, more preferably 1 or 2.
[0080] In the above equation (1), R 1 and R 2 R represents 1 With R 2 In the case of a bonded ring structure, the ring structure can have a saturated ring framework or unsaturated bonds within the ring framework. Additionally, R 1 With R 2 The resulting cyclic structure can be a structure in which alkyl groups (such as methyl or ethyl groups) are bonded to the cyclic backbone. 1 With R 2 The number of carbon atoms in the bonded ring structure is preferably 2 to 8, more preferably 2 to 6, and even more preferably 3 to 5.
[0081] From the perspective of improving the ionic conductivity of molecular crystals, R in the above equation (1) 1 and R 2 Preferred representation of R 1 With R 2 The bonded ring structure is more preferably a ring structure with a saturated ring skeleton.
[0082] The total number of carbon atoms in the above formula (1) is 2 to 16. In the manufacture of molecular crystals, from the viewpoint of promoting the crystallization of the mixture of the (A-1) molecule supply component and the alkali metal salt, the total number of carbon atoms in the above formula (1) is preferably 2 to 8, more preferably 2 to 6, and even more preferably 2 to 5.
[0083] A specific example of the (A-1) molecule is R in the above formula (1). 1 and R 2Examples of compounds that are alkyl or alkoxy groups include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, dioctyl sulfone, dimethyl sulfate, and diethyl sulfate. As R in the above formula (1)... 1 and R 2 R represents 1 With R 2 Examples of cyclic structures formed by bonding include tetrahydrothiophene-1,1-dioxide, 3-methylcyclobutane sulfone, 3-cyclobutene sulfone, 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, and 1,3,2-dioxazothiophene-2,2-dioxide. The (A-1) molecule constituting the molecular crystal can be a single type or a combination of two or more types.
[0084] (Organic molecules containing nitrogen atoms) Nitriles are preferred as organic molecules having nitrogen atoms. A preferred example of a nitrile is the molecule shown in formula (2) below.
[0085] [Chemistry 2]
[0086] (In equation (2), R) 3 R represents a hydrocarbon chain. 4 and R 5 Each group independently represents a hydrogen atom, an alkyl group, or a cyano group, wherein the total number of carbon atoms in formula (2) is 16 or less. The molecule shown in formula (2) above (hereinafter also referred to as the "(A-2) molecule") is a molecule having two or more cyano groups (-CN). R in formula (2) above... 3 It can be a saturated hydrocarbon chain or it can contain unsaturated bonds. From the perspective of obtaining molecular crystals with superior ionic conductivity, R... 3 Preferably, it represents a saturated hydrocarbon chain. R 3 The number of carbon atoms is, for example, 1 to 10, preferably 1 to 6, and more preferably 2 to 4.
[0087] In R 4 or R 5 When the alkyl group is alkyl, it can be either linear or branched. Linearity is preferred. From the viewpoint of crystallizing a molecular crystal by mixing the supply component of (A-2) molecules with an alkali metal salt, R... 4 and R 5 The number of carbon atoms in each group is preferably 0 to 3, more preferably 0 or 1.
[0088] From the viewpoint of promoting the crystallization of the mixture of the supply component of (A-2) molecule and the alkali metal salt during molecular crystal manufacturing, the total number of carbon atoms in the above formula (2) is preferably 8 or less, and more preferably 6 or less.
[0089] Specific examples of (A-2) molecules include succinic anionyl nitrile, adiponitrile, 3-hexenedionitrile, 1,3,5-pentanetricarbonyl nitrile, tert-butylmalonium nitrile, and 1,2,2,3-propanetetracarbonyl nitrile. The (A-2) molecules constituting the molecular crystal can be a single type or a combination of two or more types.
[0090] (Organic molecules containing phosphorus atoms) Examples of organic molecules containing phosphorus atoms include 1,2-bis(dimethylphosphine)ethane, 1,2-bis(diphenylphosphine)ethane, methyl(diphenyl)phosphine oxide, triphenylphosphine oxide, methyl(diphenyl)phosphine imine, and triphenylphosphine imine.
[0091] From the viewpoint of ease of manufacturing molecular crystals, regarding the organic molecule (A), it is preferable to select at least one of sulfones and nitriles. Furthermore, considering the superior ionic conductivity of the molecular crystal, it is more preferable to have a molecule (A-1), and even more preferably to have R representing the above formula (1). 1 With R 2 The cyclic structure formed by bonding is further preferably a saturated cyclic backbone.
[0092] Alkali metal salts Alkali metal salts are any salts that produce alkali metal ions; there are no particular limitations. Examples of alkali metal salts include lithium salts, sodium salts, and potassium salts.
[0093] Specific examples of alkali metal salts include Li₂CO₃, LiBr, LiCl, LiI, LiSCN, LiBF₄, LiAsF₆, LiClO₄, CH₃COOLi, CF₃COOLi, LiCF₃SO₃, LiPF₆, LiC(CF₃SO₂)₃, and lithium bis(fluorosulfonyl)imide (Li + (FSO2)2N - ), Lithium bis(trifluoromethanesulfonyl)imide (Li + (CF3SO2)2N - Lithium salts such as lithium(fluorosulfonyl) and lithium(trifluoromethanesulfonyl)imide; and salts of the anions of these lithium salts with alkali metals other than lithium (e.g., sodium, potassium, etc.). From the perspective of obtaining molecular crystals with high ion dissociation and higher ion conductivity, lithium salts or sodium salts are preferred among these.
[0094] From the perspective of further improving the ionic conductivity of the molecular crystal, the alkali metal salt constituting the molecular crystal preferably includes an imide-based alkali metal salt. Among them, from the perspective of high ionic dissociation, imide-based lithium salts or imide-based sodium salts are preferred.
[0095] As an imide-based lithium salt, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, or lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide are particularly preferred, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethanesulfonyl)imide are more preferred, and lithium bis(fluorosulfonyl)imide is even more preferred.
[0096] As an imide-based sodium salt, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, or sodium trifluoromethanesulfonylimide are preferred, more preferably sodium bis(fluorosulfonyl)imide or sodium bis(trifluoromethanesulfonyl)imide, and even more preferably sodium bis(fluorosulfonyl)imide.
[0097] The molecular weight of the alkali metal salt is, for example, 500 or less, preferably 400 or less, more preferably 350 or less, and even more preferably 300 or less. Regarding the lower limit of the molecular weight of the alkali metal salt, it is, for example, 20 or more, preferably 50 or more, more preferably 100 or more, and even more preferably 150 or more. The alkali metal salt constituting the molecular crystal can be a single type or two or more types.
[0098] The melting point of alkali metal salts is, for example, 60°C or higher, preferably 70°C or higher, and more preferably 80°C or higher. There is no particular upper limit to the melting point of alkali metal salts; for example, it can be 300°C or lower, or even 250°C or lower.
[0099] <The manufacture of molecular crystals> There is no particular limitation on the method for manufacturing the molecular crystal that constitutes the (Y) component of the composite electrolyte of this disclosure. For example, when using an organic solid electrolyte containing (A) organic molecules and alkali metal salts as constituent units as the (Y) component, it is possible to manufacture the molecular crystal using the supply component of (A) organic molecules (hereinafter also referred to as "(A) organic matter") and the alkali metal salt.
[0100] Molecular crystals comprising (A) organic molecules and alkali metal salts as building blocks are preferably obtained by heating a mixture of (A) organic molecules and alkali metal salts. Specifically, they are preferably manufactured by a method comprising a mechanical mixing step and a heating step.
[0101] Mechanical mixing process: A process in which organic matter (A) and an alkali metal salt are mixed while mechanical energy is applied to obtain a mixture. Heating process: The process of heating the mixture obtained through mechanical mixing. The following is a detailed description of each process.
[0102] <Mechanical Mixed Processes> In a mechanical mixing process, the organic compound (A) and the alkali metal salt are mixed while mechanical energy is applied to them through means such as impact, shearing, compression, and friction. This preferably causes a change in the physicochemical properties of the organic compound (A), the alkali metal salt, or both. It should be noted that, in this specification, the process of mixing substances while applying mechanical energy is also referred to as "mechanical mixing."
[0103] The mixing ratio of organic compound (A) to alkali metal salt can be set according to the types of organic compound (A) and alkali metal salt, and is not particularly limited. Regarding the mixing ratio of organic compound (A) to alkali metal salt, for example, relative to 1 mole of alkali metal salt, the amount of organic compound (A) can be set to 0.1 to 10 moles. Regarding the mixing ratio of organic compound (A) to alkali metal salt, relative to 1 mole of alkali metal salt, it is preferable to set the amount of organic compound (A) to 0.2 to 5 moles, more preferably to 0.25 to 4 moles, and even more preferably to 0.5 to 2 moles.
[0104] It should be noted that, during the manufacture of molecular crystals, without impairing the effects of this disclosure, substances different from the organic compound and alkali metal salt (e.g., sulfur-containing organic molecules different from the organic compound) can be used as constituent units of the crystal lattice. However, considering the ionic conductivity and ease of manufacture of the molecular crystal, it is preferable to minimize the amount of the substance different from the organic compound and alkali metal salt used. Specifically, relative to 1 mole of the total amount of the organic compound and alkali metal salt, the amount of the substance different from the organic compound and alkali metal salt used is preferably 0.1 moles or less, more preferably 0.05 moles or less.
[0105] There are no particular limitations on the method for mixing (A) organic matter with an alkali metal salt while applying mechanical energy. In the mechanical mixing process, the mixing of (A) organic matter with an alkali metal salt can be performed using various equipment such as ball mills, bead mills, mixers, homogenizers, crushers, homogenizing mixers, and disperser-type mixers. Furthermore, in the case of small-scale manufacturing of molecular crystals, the mechanical mixing of (A) organic matter with an alkali metal salt can also be performed using a mortar and pestle. The mechanical mixing of (A) organic matter with an alkali metal salt can be performed dry or wet. Moreover, the mechanical mixing of (A) organic matter with an alkali metal salt can be performed at room temperature or at low temperature. For example, if the melting point of (A) organic matter is below room temperature, the liquid state of (A) organic matter can be mechanically mixed with the alkali metal salt. Alternatively, the solid state of (A) organic matter can be mechanically mixed with the alkali metal salt at a temperature below the melting point of (A) organic matter.
[0106] It should be noted that the mechanical mixing of (A) organic matter and alkali metal salt can be carried out while heating is being performed. However, in order to suppress the volatilization and sublimation of (A) organic matter, the mechanical mixing process can be carried out at a temperature lower than the heating temperature in the subsequent heating process. Specifically, the mechanical mixing process is carried out, for example, at a temperature below 50°C, preferably at a temperature below 40°C, and more preferably at a temperature below 35°C. The time for mechanical mixing depends on the amount and type of (A) organic matter and alkali metal salt used, and may be, for example, 1 to 60 minutes, or 1 to 30 minutes.
[0107] The melting point of the mixture of organic (A) and alkali metal salt obtained by mechanical mixing (hereinafter also simply referred to as the "mixture") is preferably 40°C or higher, more preferably 50°C or higher, and even more preferably 55°C or higher. Furthermore, from the viewpoint of suppressing the decomposition of molecular crystals accompanying the volatilization or sublimation of organic (A) or organic (A) molecules during the heating process following the mechanical mixing step, the melting point of the mixture is preferably 110°C or lower, more preferably 100°C or lower, and even more preferably 95°C or lower. In this specification, the melting point of the mixture of organic (A) and alkali metal salt is a value obtained by differential scanning calorimetry (DSC). Details of the measurement method are as described in the examples described later.
[0108] <Heating Process> In the heating process, after the aforementioned mechanical mixing process, the mixture obtained through the mechanical mixing process is heated. The method of heating the mixture is not particularly limited. The heating temperature of the mixture can be appropriately set according to the type of (A) organic compound and alkali metal salt used in the raw materials. From the viewpoint of making the (A) organic compound and alkali metal salt in the mixture more homogeneous, in this heating process, it is preferable to heat the mixture at a temperature above the melting point of the mixture of (A) organic compound and alkali metal salt obtained through mechanical mixing. By setting the heating temperature above the melting point of the mixture, the mixture melts, thereby promoting the homogeneous mixing of the (A) organic compound and the alkali metal salt.
[0109] Regarding the temperature for heating the mixture, from the viewpoint of achieving homogenization of the (A) organic matter and alkali metal salt in the mixture by melting the mixture, it is preferable to set a temperature higher than the melting point of the mixture. Furthermore, from the viewpoint of promoting homogenization of the (A) organic matter and alkali metal salt in the mixture, the heating temperature of the mixture is more preferably set to a temperature at least 5°C higher than the melting point (in °C) of the mixture, and even more preferably at least 7°C higher. Regarding the upper limit of the heating temperature of the mixture, from the viewpoint of suppressing the volatilization and sublimation of the components contained in the mixture, when the melting point of the mixture is expressed as Mp (in °C), it is preferably set to (Mp+20)°C or lower, and more preferably to (Mp+15)°C or lower. The heating time is not particularly limited as long as it is sufficient to homogenize the (A) organic matter and alkali metal salt in the mixture. The heating time is, for example, 1 minute to 3 hours, preferably 15 minutes to 2 hours, and more preferably 30 minutes to 2 hours. Furthermore, the heat treatment can generally be carried out under normal pressure, but it can be carried out under pressure or under reduced pressure.
[0110] When heating the mixture, it is preferable to further homogenize (A) the organic matter and the alkali metal salt by stirring the mixture simultaneously. The stirring method is not particularly limited; examples include magnetic stirrers, stirring rods, mixers with stirring blades, and external circulation mixers. Alternatively, stirring can be performed using mechanical mixing operations that provide greater shear force, such as homogenizers, disperser-type mixers, and homogenizers.
[0111] After heating a mixture containing (A) organic matter and an alkali metal salt, the temperature of the heated mixture is lowered, thereby crystallizing the heated mixture to obtain the target molecular crystal. When lowering the temperature of the heated mixture, the mixture can be cooled slowly (e.g., slowly lowering the temperature at room temperature over 1 to 48 hours). Alternatively, the heated mixture can be cooled rapidly (e.g., briefly placing the heated mixture in a thermostat at a temperature lower than room temperature (e.g., below 15°C)). From the viewpoint of properly carrying out crystallization of the heated mixture, it is preferable to cool the heated mixture by slowly lowering its temperature. The fact that the product obtained by this manufacturing method is a molecular crystal containing (A) organic molecules and an alkali metal salt can be detected by performing powder X-ray diffraction analysis of the product. Details of the analysis method are as described in the examples described later.
[0112] It should be noted that, according to the manufacturing method that includes a mechanical mixing process and a heating process, it is believed that during the manufacture of molecular crystals, intermolecular interactions occur between alkali metal ions from alkali metal salts and (A) organic matter through mechanical mixing prior to heat treatment. Therefore, it is believed that in the manufacturing method of performing heat treatment after mechanical mixing, the sublimation and volatilization of (A) organic matter are suppressed during heat treatment, thereby suppressing the inhomogeneity of the molecular crystal composition. Furthermore, it is believed that by suppressing the inhomogeneity of the molecular crystal composition and forming a uniform ion conduction pathway, it is possible to manufacture molecular crystals exhibiting excellent ion conductivity.
[0113] In the composite electrolyte, from the viewpoint of sufficiently reducing the interparticle resistance of the inorganic solid electrolyte, thereby improving ion conductivity, and from the viewpoint of ensuring good formability of the composite electrolyte, the content ratio of the molecular crystal as component (Y) relative to the total amount of the composite electrolyte is preferably 1 volume% or more, more preferably 5 volume% or more, further preferably 15 volume% or more, even more preferably 25 volume% or more, even more preferably 30 volume% or more, and even more preferably 35 volume% or more. Furthermore, from the viewpoint of effectively utilizing the characteristics of the inorganic solid electrolyte to obtain a composite electrolyte with high ion conductivity, the upper limit of the content ratio of the molecular crystal relative to the total amount of the composite electrolyte is preferably 99 volume% or less, more preferably 98 volume% or less, even more preferably 95 volume% or less, and even more preferably 90 volume% or less.
[0114] It should be noted that the composite electrolyte of this disclosure may further include components other than the inorganic solid electrolyte and molecular crystals, to the extent that the effects of this disclosure are not impaired. Examples of other components include molecular crystals different from the molecular crystals of this disclosure (i.e., component (Y)), polymeric solid electrolytes, polymeric gel electrolytes, binders, etc. However, considering the ionic conductivity and ease of manufacture of the composite electrolyte, it is preferable to use as little of the other components as possible. Specifically, the content of the other components is preferably 1% by volume or less, more preferably 0.5% by volume or less, relative to the total amount of the inorganic solid electrolyte and molecular crystals.
[0115] <Manufacturing Method of Composite Electrolytes> The composite electrolyte of this disclosure can be manufactured by mixing an inorganic solid electrolyte as component (X) with a molecular crystal as component (Y). Specifically, the composite electrolyte of this disclosure is preferably manufactured by a method comprising a mixing step and a heating step.
[0116] Mixing process: The process of mixing inorganic solid electrolytes and molecular crystals to obtain a mixture. Heating process: The process of heating a mixture of inorganic solid electrolytes and molecular crystals. <Mixed Process> In the mixing process of manufacturing composite electrolytes, any method is acceptable as long as it allows for uniform mixing of the inorganic solid electrolyte and the molecular crystal. The mixing of the inorganic solid electrolyte and the molecular crystal can be dry or wet. Dry mixing is preferred. According to the mechanical mixing process, it is preferable that the molecular crystal, as a raw material, can be melted using the heat of mechanical mixing and uniformly mixed with the inorganic solid electrolyte, and that a composite electrolyte with sufficiently low porosity can be obtained without using a solvent during mixing. As a specific method of mechanical mixing, the description of the mechanical mixing process in the method for manufacturing molecular crystals can be applied.
[0117] The mixing ratio of inorganic solid electrolyte and molecular crystal can be set according to the types of inorganic solid electrolyte and molecular crystal, and is not particularly limited. From the viewpoint of improving ion conductivity and formability in a balanced way, the mixing ratio of inorganic solid electrolyte to molecular crystal, in terms of volume ratio, is preferably set as inorganic solid electrolyte: molecular crystal = 1:99 to 99:1, more preferably 5:95 to 95:2, even more preferably 15:85 to 90:10, even more preferably 25:75 to 90:10, even more preferably 30:70 to 90:10, and even more preferably 35:65 to 90:10.
[0118] <Heating Process> In the heating process, after the above-mentioned mixing process, the mixture of inorganic solid electrolyte and molecular crystal obtained through the mixing process is heated. It is believed that through this heating process, the gaps between the inorganic solid electrolyte are filled by the molecular crystal, thereby reducing the porosity. As a result, the interfacial resistance decreases, and a composite electrolyte with excellent ion conductivity can be obtained.
[0119] In the heating process, the mixture obtained through the mixing process (typically granular) can be directly heated. Alternatively, a mixture of inorganic solid electrolyte and molecular crystals can be molded, and the resulting molded body can be heated. When heating the molded body, the molding method is not particularly limited, and known methods such as extrusion molding, injection molding, pressure molding, casting, die casting, and tape casting can be used. However, considering minimizing the porosity of the composite electrolyte and facilitating the formation of ion conduction pathways, pressure molding is preferred. The shape of the molded body is not particularly limited and can be appropriately set according to the shape of the energy storage device to be applied. For example, the shape of the molded body can be rectangular or circular.
[0120] The heating temperature for heating a mixture of inorganic solid electrolyte and molecular crystal can be appropriately set according to the type of inorganic solid electrolyte and molecular crystal used in the raw materials. From the viewpoint of obtaining a composite electrolyte (i.e., a solid electrolyte) with low porosity by using molecular crystals to fill the gaps in the inorganic solid electrolyte, it is preferable to heat the mixture at a temperature at which the molecular crystals do not seep out of the mixture during heating.
[0121] Specifically, in the heating process of manufacturing the composite electrolyte, it is preferable to heat the mixture of the inorganic solid electrolyte and the molecular crystal at or near the melting point of the molecular crystal (for example, in the case of a molecular crystal containing (A) organic molecules and alkali metal salts as constituent units, the melting point of the mixture of (A) organic molecules and alkali metal salts as raw materials). From the viewpoint of maintaining the gaps between the inorganic solid electrolyte and the molecular crystal in the mixture, if the melting point of the molecular crystal is denoted as Mr (unit: °C), then the heating temperature of the mixture of the inorganic solid electrolyte and the molecular crystal is preferably set to a range of (Mr ± 15) °C, and more preferably to a range of (Mr ± 10) °C.
[0122] The heating time is, for example, 1 to 72 hours, preferably 2 to 48 hours, and more preferably 5 to 36 hours. Furthermore, the heat treatment can be carried out under normal pressure, or under pressure or depressurization. When lowering the temperature of the mixture after heating, the mixture can be cooled slowly (e.g., air-cooled) or rapidly cooled using a cooler or the like. It should be noted that if the heated mixture is a molded body, this molded body can be directly used as the solid electrolyte layer of a battery storage device. Alternatively, multiple molded bodies can be stacked to form the solid electrolyte layer of a battery storage device. When the composite electrolyte of this disclosure is used as a molded body, the thickness of the molded body is, for example, 5 to 5000 mm. m m, preferably 5 to 3500 m m, more preferably 10 to 3000 m m.
[0123] The composite electrolyte obtained as described above exhibits high ionic conductivity. Therefore, by using the composite electrolyte of this disclosure as the electrolyte material in a storage device, a storage device with high ionic conductivity can be obtained. Specifically, for a thickness of 1000 mm incorporating the composite electrolyte of this disclosure... m Approximately m (specifically, 1000±50 m) m The ionic conductivity of the molded body (m) measured by AC impedance spectroscopy at 25°C is preferably 1×10⁻⁶. -6 S / cm or higher. From the viewpoint of obtaining a high-performance energy storage device, an ionic conductivity of 2 × 10⁻⁶ is more preferable under the same conditions. -6S / cm or higher, more preferably 5×10 -6 S / cm or higher. Ionic conductivity can be determined by AC impedance measurement. Details of the measurement method are as described in the examples below.
[0124] Energy Storage Equipment The energy storage device disclosed herein (hereinafter also referred to as "the device") includes the composite electrolyte of the present disclosure. Examples of the device include secondary batteries and capacitors. When the device is a secondary battery, one option is an all-solid-state battery, and from the perspective of excellent ion conductivity, lithium-ion secondary batteries or sodium-ion secondary batteries are preferred.
[0125] An all-solid-state secondary battery, which is one embodiment of this device, will be described. An all-solid-state secondary battery is a laminate comprising electrodes including a positive electrode and a negative electrode, and a solid electrolyte layer, wherein the solid electrolyte layer is disposed between the positive and negative electrodes in such a way that it contacts the electrodes. The materials constituting the positive and negative electrodes are not particularly limited, and can be appropriately selected from materials known as electrode materials for secondary batteries. For example, in the case of a lithium-ion secondary battery, aluminum, stainless steel, or other metal foils can be used as the positive electrode current collector. Copper foil, lithium foil, or other metal foils can be used as the negative electrode current collector.
[0126] In all-solid-state secondary batteries, the solid electrolyte layer is formed from the composite electrolyte of this disclosure (i.e., a composite electrolyte comprising an inorganic solid electrolyte and molecular crystals). The thickness of the solid electrolyte layer is not particularly limited and can be appropriately set according to the application of the secondary battery. For example, the thickness of the solid electrolyte layer is 5 to 5000 mm. m m, preferably 5 to 3500 m m, more preferably 10 to 3000 m m.
[0127] There are no particular limitations on the method for manufacturing all-solid-state secondary batteries, and known methods can be appropriately adopted depending on the battery structure, etc. For example, a solid electrolyte layer formed by sandwiching a composite electrolyte of the present disclosure with a positive electrode and a negative electrode can be used, preferably subjected to a pressure treatment for bonding, thereby manufacturing a laminate having a positive electrode, a solid electrolyte layer, and a negative electrode. Alternatively, an electrolyte material containing a particulate composite electrolyte can be contained in a container by sandwiching a positive electrode and a negative electrode, and the container can be subjected to a heat treatment to obtain the aforementioned composite electrolyte, preferably subjected to a pressure treatment for bonding, thereby manufacturing a laminate having a positive electrode, a solid electrolyte layer, and a negative electrode. The laminate having a positive electrode, a solid electrolyte layer, and a negative electrode is usually housed in a casing and used as a secondary battery.
[0128] It should be noted that there is no particular limitation on the charge carriers used for ion conduction in this device. Alternatively, this device can also be a capacitor. One possible configuration for a capacitor is as follows: it comprises an anode, a cathode, and a solid electrolyte layer, with the solid electrolyte layer disposed between the anode and cathode in such a way that it is connected to the electrodes.
[0129] Energy storage devices equipped with a solid electrolyte layer formed using the composite electrolyte of this disclosure can be applied to a variety of uses. Specifically, they can be used as power sources in various mobile devices such as mobile phones, personal computers, smartphones, game consoles, and wearable terminals; various mobile vehicles such as electric vehicles, hybrid vehicles, robots, and drones; and various electrical and electronic devices such as digital cameras, camcorders, music players, power tools, and home appliances.
[0130] Example The present disclosure will now be described in detail based on the embodiments. It should be noted that the present disclosure is not limited to these embodiments. Unless otherwise specified, "parts" and "%" refer to "parts by volume" and "% by volume," respectively.
[0131] Manufacturing and Physical Properties of Inorganic Solid Electrolytes [Manufacturing Example 1] 1. Manufacturing of Inorganic Solid Electrolyte ISE-1 Using the molar ratio shown in Manufacturing Example 1 of Table 1 (Li:In:Zr:Si:P = 1.25:0.20:1.80:0.05:2.95), 4.000 g of layered zirconium phosphate (Zr(HPO4)2·nH2O), 0.432 g of zirconium hydroxide, 0.415 g of lithium carbonate (manufactured by Fujifilm and Wooko Pure Chemical Industries Co., Ltd.), 0.027 g of silicon dioxide (manufactured by Fujifilm and Wooko Pure Chemical Industries Co., Ltd.), and 0.25 g of indium oxide (manufactured by Fujifilm and Wooko Pure Chemical Industries Co., Ltd.) were weighed as the supply components, placed in a mortar, and 25 g of pure water was added for wet mixing to obtain a mixture (mixing process). After drying the obtained mixture at 100°C for 2 hours, it was transferred to an alumina crucible (capacity 30 mL), heated to 1250°C over 5.5 hours, and held for 5 hours for calcination (calcination process). Then, the mixture was cooled to room temperature (25°C) to obtain a calcined product. The calcined product was then pulverized using a mortar and pestle to obtain the inorganic solid electrolyte ISE-1. It should be noted that in each manufacturing example, the value of n in Zr(HPO4)2·nH2O was set to 1.0.
[0132] 2. Confirmation of crystallinity by powder X-ray diffraction. The obtained inorganic solid electrolyte ISE-1 was subjected to powder X-ray diffraction analysis using an X-ray diffraction apparatus (Bruker AXS, D8 ADVANCE). It should be noted that Cu Kα was used as the X-ray source, with an applied voltage of 40 kV and a current of 40 mA. Regarding the measurement conditions, the measurement range was set to 2θ = 10–80°, the scan rate to 2.5° / min, and the step angle to 0.01°. The results confirmed that the main crystalline phase of the inorganic solid electrolyte ISE-1 belongs to the monoclinic or trigonal LiZr₂P₃O₃ system. 12 The inorganic solid electrolyte ISE-1 has a NASICON-type crystal structure.
[0133] 3. Determination of median particle size in volumetric reference For the inorganic solid electrolyte ISE-1, a 1% (w / w) dispersion was prepared by diluting it with pure water in a 30 mL sample vial. The diluted dispersion was then irradiated with ultrasound at 1 kHz for 10 minutes. The dispersion immediately after ultrasound irradiation was used as the test sample, and the volumetric median particle size (D50) of the inorganic solid electrolyte ISE-1 was measured using a laser diffraction-scattering particle size analyzer MT-3000 (manufactured by Microtrac) at room temperature (25°C). Two particle size measurements were performed, and the average value was used as the volumetric median particle size of the inorganic solid electrolyte ISE-1. The volumetric median particle size of the inorganic solid electrolyte ISE-1 was 1.4. m m.
[0134] 4. Determination of ionic conductivity A die containing module 11, upper punch 12, and lower punch 13 is used (see reference). Figure 1 Sample particles were prepared in a drying chamber with a dew point below -40°C. First, a module 11 containing 0.150 g of inorganic solid electrolyte ISE-1 was placed on the lower punch 13, and the upper punch 12 was placed on the module 11. The inorganic solid electrolyte ISE-1 was compressed for 1 minute using a hydraulic press at a pressure of 10 MPa, yielding a sample with a diameter of 1 cm and a thickness of 1000 mm. m The sample particles were spherical in shape. Then, the sample particles were sealed into an all-solid-state battery evaluation cell (manufactured by Hosen Co., Ltd., KP-SolidCell) in a drying chamber with a dew point below -40°C.
[0135] Using an all-solid-state battery evaluation unit containing sample particles, the resistance value at 25°C was measured by AC impedance spectroscopy. Using the obtained resistance value, the ionic conductivity (σ) was calculated using the following mathematical formula (1).
[0136] σ = L / (R×S) …(1) (In mathematical formula (1), σ represents ionic conductivity (unit: S / cm), R represents electrical resistance (unit: Ω), and S represents the cross-sectional area of the sample particles (unit: cm²). 2 L represents the distance between electrodes (unit: cm). The ionic conductivity (σ) of inorganic solid electrolyte ISE-1 at 25℃ ISE ) is 2.0 × 10 -7 S / cm.
[0137] 5. Determination of porosity The all-solid-state battery evaluation unit, after ion conductivity measurement, was disassembled, and the inorganic solid electrolyte ISE-1 obtained in Manufacturing Example 1 was extracted. The thickness (L) of the inorganic solid electrolyte ISE-1 was measured using a film thickness gauge (manufactured by MITUTOYO Co., Ltd.), and the result was 928. m m. Additionally, the density (D) of the inorganic solid electrolyte ISE-1 is calculated using the following mathematical formula (2). ISE ).
[0138] D ISE = M ISE / (S) ISE ×L ISE …(2) (In mathematical expression (2), D) ISE Density of inorganic solid electrolytes (unit: g·cm³) -3 M ISE S represents the mass (in grams) of an inorganic solid electrolyte. ISE This indicates the contact area between the electrode and the inorganic solid electrolyte (unit: cm²). 2 ), L ISE This indicates the thickness of the inorganic solid electrolyte (unit: cm). Solid electrolyte ISE-1 is M ISE =0.015, S ISE =0.785, the density (D) obtained by the above mathematical formula (2) ISE The value is 2.06 (g·cm). -3 ).
[0139] The density (D) of the inorganic solid electrolyte ISE-1 obtained above ISE The porosity (φ) of the inorganic solid electrolyte ISE-1 is calculated using the following mathematical formula (3). ISE The result was 35%.
[0140] φ ISE =(1-D ISE / D′ ISE )×100 …(3) (In mathematical expression (3), φ)ISE D represents porosity (unit: %) ISE Density of inorganic solid electrolytes (unit: g·cm³) -3 ), D′ ISE The theoretical density of the inorganic solid electrolyte is given (the theoretical density of inorganic solid electrolyte ISE-1 is 3.17, unit: g·cm³). -3 ). It should be noted that the theoretical density D′ ISE The information of the crystal phase identified by XRD is obtained by the following mathematical formula (4).
[0141] D′ ISE = N / V …(4) (In mathematical formula (4), N represents the atomic mass in the unit cell of the inorganic solid electrolyte (unit: g), and V represents the volume of the unit cell of the inorganic solid electrolyte (unit: cm). 3 ). For the inorganic solid electrolyte ISE-1, N = 4.79 × 10⁻⁶ -21 V = 1.51 × 10 -21 .
[0142] [Manufacturing Examples 2-4] As shown in Table 1, the types and amounts of raw materials were changed, and the same operations as in Manufacturing Example 1 were performed to obtain inorganic solid electrolytes (referred to as "Inorganic Solid Electrolyte ISE-2", "Inorganic Solid Electrolyte ISE-3", and "Inorganic Solid Electrolyte ISE-4", respectively). Furthermore, for the inorganic solid electrolytes ISE-2, ISE-3, and ISE-4 obtained in each manufacturing example, the median particle size and ionic conductivity (σ) based on volume were measured in the same manner as in Manufacturing Example 1. ISE The results are shown in Table 1. Furthermore, for inorganic solid electrolytes ISE-2, ISE-3, and ISE-4, powder X-ray diffraction measurements were performed in the same manner as in Manufacturing Example 1. The results showed that the main crystal phase of inorganic solid electrolytes ISE-2 and ISE-3 belonged to the monoclinic or trigonal Na3Zr2Si2PO4 system. 12 The main crystalline phase of the inorganic solid electrolyte ISE-4 belongs to the monoclinic or trigonal LiZr2P3O system. 12 Based on these results, it was confirmed that inorganic solid electrolytes ISE-2, ISE-3, and ISE-4 possess a NASICON-type crystal structure.
[0143] [Table 1]
[0144] Manufacturing and Physical Properties of Organic Solid Electrolytes [Manufacturing Example 5] 1. Manufacturing of molecular crystals (organic solid electrolyte OSE-1) In a drying chamber with a dew point below -40°C, 0.1616 g of succinate (manufactured by Tokyo Chemical Industry Co., Ltd.) as an organic molecule and 0.1384 g of lithium bis(fluorosulfonyl)imide (manufactured by Kanto Chemical Co., Ltd.) as an alkali metal salt were measured in a molar ratio (organic molecule: alkali metal salt = 2:1) as shown in Manufacturing Example 5 of Table 2. The mixture was mechanically mixed in a mortar at room temperature (25°C) for 5 minutes to obtain a mixture (mechanical mixing process). The melting point of the mixture was measured using a differential scanning calorimeter (manufactured by TA Instruments, DSC250, measurement atmosphere: nitrogen atmosphere) at a heating rate of 10°C per minute. A large endothermic peak (melting point) was observed at 60°C.
[0145] Transfer the mixture to a tubular flask and stir with a magnetic stirrer set to 80°C for 1 hour to ensure uniform dissolution (heating step). Then, cool the resulting melt to room temperature to obtain a white solid.
[0146] 2. Confirmation of crystallinity by powder X-ray diffraction. The obtained white solid was subjected to powder X-ray diffraction (PXRD) measurements using an X-ray diffraction apparatus (Bruker AXS, D8 ADVANCE). It should be noted that Cu Kα was used as the X-ray source, with an applied voltage of 40 kV and a current of 40 mA. The measurement range was set to 2θ = 5–60°, the scan rate to 2.3° / min, and the step angle to 0.02°. The presence of sharp peaks in the X-ray diffraction spectrum within the measurement range indicates that the sample (white solid) is crystalline. Therefore, if an X-ray diffraction spectrum with sharp peaks within the measurement range, different from both the organic molecules and the alkali metal salt used as raw materials, is obtained, it is determined that a molecular crystal composed of organic molecules and an alkali metal salt has been formed. It should be noted that if the organic molecules used as raw materials are liquid at room temperature, and an X-ray diffraction spectrum different from that of the lithium salt is observed, it is determined that a molecular crystal composed of lithium salt and organic molecules has been formed.
[0147] The white solid obtained by the above method was subjected to powder X-ray diffraction analysis. The results showed that the X-ray diffraction spectrum had sharp peaks within the measurement range and was different from that of the raw material. This confirms that the obtained white solid is crystalline, that is, it is a molecular crystal composed of organic molecules and alkali metal salts (which is referred to as "organic solid electrolyte OSE-1").
[0148] 3. Determination of ionic conductivity use Figure 1 The compression mold 10 shown is used to prepare sample particles in a drying chamber with a dew point below -40°C. First, a mold 11 containing 0.0200 g of white solid (organic solid electrolyte OSE-1) is placed on the lower punch, and an upper punch 13 is placed on the mold 11. The white solid is compressed for 1 minute using a hydraulic press at a pressure of 10 MPa to obtain a sample with a diameter of 1 cm and a thickness of 200 mm. m The sample particles were spherical in shape. Then, the sample particles were sealed into an all-solid-state battery evaluation cell (manufactured by Hosen Co., Ltd., KP-SolidCell) in a drying chamber with a dew point below -40°C.
[0149] Ionic conductivity was measured using an all-solid-state battery evaluation unit containing sample particles. In the ionic conductivity measurement, the sealed unit containing sample particles was first heat-treated in a constant-temperature bath at 40°C (corresponding to the heat treatment temperature in Table 2), while the resistance value was measured by AC impedance spectroscopy. The heat treatment was stopped when the resistance value stabilized. Next, the resistance value at 25°C was measured by AC impedance spectroscopy. Using the obtained resistance value, the ionic conductivity (σ) was calculated using the above mathematical formula (3). It should be noted that the AC impedance spectroscopy used to calculate the ionic conductivity was performed after the unit was held at the measurement temperature in a constant-temperature bath for 2 hours.
[0150] The ionic conductivity (σ) of organic solid electrolyte OSE-1 at 25℃ OSE The value is 3.9 × 10 -5 S / cm.
[0151] 4. Determination of porosity The all-solid-state battery evaluation unit, after ion conductivity measurement, was disassembled, and the organic solid electrolyte OSE-1 obtained in Manufacturing Example 5 was extracted. The thickness (L) of the organic solid electrolyte OSE-1 was measured using a film thickness gauge (manufactured by MITUTOYO Co., Ltd.) OSE The result was 171. m m. Additionally, the density (D) of the organic solid electrolyte is calculated using the following mathematical formula (5). OSE ).
[0152] D ОSE =M ОSE / (S) ОSE ×L ОSE …(5) (In mathematical expression (5), D) OSE Density of organic solid electrolytes (unit: g·cm³) -3 M OSEThe value of S represents the mass of the organic solid electrolyte (in grams), and S represents the contact area between the electrode and the organic solid electrolyte (in cm²). 2 ), L OSE This indicates the thickness of the organic solid electrolyte (unit: cm). For organic solid electrolyte OSE-1, M OSE =0.002, S OSE =0.785, the density (D) obtained by the above mathematical formula (5) OSE The value was 1.49 (g·cm). -3 ).
[0153] The density (D) of the organic solid electrolyte OSE-1 obtained above OSE The porosity (φ) of the organic solid electrolyte OSE-1 is calculated using the following mathematical formula (6). OSE The result was 0%.
[0154] φ ОSE =(1-D ОSE / D′ ОSE )×100 …(6) (In mathematical expression (6), φ) OSE D represents porosity (unit: %) OSE Density of organic solid electrolytes (unit: g·cm³) -3 ), D′ OSE (This represents the theoretical density of an organic solid electrolyte.) It should be noted that the theoretical density D′ OSE The information of the crystal phase identified by XRD is obtained by the following mathematical formula (7).
[0155] D′ OSE = N / V …(7) (In mathematical formula (7), N represents the atomic mass in the unit cell of the organic solid electrolyte (unit: g), and V represents the volume of the unit cell of the organic solid electrolyte (unit: cm). 3 ). The organic solid electrolyte OSE-1 has N = 1.15 × 10⁻⁶. -21 V = 7.71 × 10 -22 The theoretical density of the organic solid electrolyte OSE-1 is 1.49 g·cm³. -3 ).
[0156] [Manufacturing Examples 6-7] The types and amounts of raw materials, as well as the heating temperature of the mixture in the heating process, were changed as described in Table 2. Otherwise, the same operation as in Manufacturing Example 5 was performed to obtain a white solid.
[0157] For the white solids obtained in each manufacturing example, powder X-ray diffraction was performed in the same manner as in manufacturing example 5. The results showed that the X-ray diffraction spectra had sharp peaks within the measurement range and were different from those of the raw materials. Therefore, it was confirmed that each white solid was a molecular crystal composed of organic molecules and alkali metal salts (referred to as "organic solid electrolyte OSE-2", "organic solid electrolyte OSE-3", and "organic solid electrolyte OSE-4", respectively).
[0158] In addition, using the white solids (organic solid electrolyte OSE-2, organic solid electrolyte OSE-3, and organic solid electrolyte OSE-4) of each manufacturing example, the ionic conductivity (σ) at 25°C was measured as described in Table 2. OSE The melting point and ionic conductivity (σ) of the mixture of organic molecules and alkali metal salts obtained through a mechanical mixing process were determined. OSE The results of the determination of ionic conductivity are shown in Table 2. In addition, after the determination of ionic conductivity, the porosity of the organic solid electrolyte was determined using the same method as in Manufacturing Example 5. The results showed that the porosity (φ) of the organic solid electrolytes OSE-2 and OSE-3 were... OSE All were 0%.
[0159] [Table 2]
[0160] Details of the compounds used in Table 2 are shown below.
[0161] •SN: Butadionitrile (manufactured by Tokyo Chemical Industry Co., Ltd.) •SL: Sulfolane (manufactured by Tokyo Chemical Industry Co., Ltd.) •AdN: Adiponitrile (manufactured by Fujifilm and Wako Pure Chemical Industries, Ltd.) • LiFSI: Lithium bis(fluorosulfonyl)imide [Manufactured by Kanto Chemical Co., Ltd.] • NaFSI: Sodium bis(fluorosulfonyl)imide [Manufactured by Fujifilm and Wako Pure Chemical Industries, Ltd.] Manufacturing and Evaluation of Composite Electrolytes [Example 1] 1. Manufacturing of composite electrolyte HSE-1 In a drying chamber with a dew point below -40°C, Li was weighed according to the mass ratio (inorganic solid electrolyte: organic solid electrolyte = 50:50 vol%) shown in Example 1 of Table 3. 1.25 In 0.2 Zr 1.8 Si 0.05 P 2.95 O 120.200 g of inorganic solid electrolyte ISE-1 obtained in Manufacturing Example 1 and 0.0938 g of organic solid electrolyte OSE-1 obtained in Manufacturing Example 5 were mechanically mixed in a mortar at room temperature (25°C) to obtain a mixture (mixing process).
[0162] use Figure 1 The mold 10 shown is used to produce sample particles consisting of a mixture of inorganic solid electrolyte and organic solid electrolyte in a drying chamber with a dew point below -40°C through the following steps.
[0163] First, a module 11 containing 0.150g of the mixture is placed on the lower punch 13, and an upper punch 12 is placed on the module 11. The mixture is then compressed for 1 minute using a hydraulic press at a pressure of 10MPa to obtain a product with a diameter of 1cm and a thickness of 1000mm. m The sample particles are round in shape and have a diameter of m.
[0164] Next, the sample particles were sealed into an all-solid-state battery evaluation unit (manufactured by Hosen Co., Ltd., KP-SolidCell) in a drying chamber with a dew point below -40°C and then sealed. The all-solid-state battery evaluation unit containing the sample particles was then heat-treated in a constant temperature bath at 55°C (corresponding to the temperature in the heating process in Table 3) (heating process). During the heat treatment, the resistance value was measured by AC impedance measurement. The heat treatment was ended when the resistance value stabilized, and the battery was air-cooled to 25°C, thereby obtaining the composite electrolyte (which was designated as composite electrolyte HSE-1).
[0165] 2. Evaluation (1) Determination of ionic conductivity For the composite electrolyte HSE-1, the ionic conductivity (σ) at 25°C was measured using the same method as in Manufacturing Example 1. SE The result was 1.9 × 10⁻⁶. -4 S / cm.
[0166] (2) Determination of porosity The all-solid-state battery evaluation unit, after ion conductivity measurement, was disassembled, and the composite electrolyte HSE-1 obtained in Example 1 was extracted. The thickness (L) of the composite electrolyte was measured using a film thickness gauge (manufactured by MITUTOYO Co., Ltd.) SE The result was 819. m m. Additionally, the density (D) of the composite electrolyte HSE-1 is calculated using the following mathematical formula (8). SE ).
[0167] D SE = M SE / (S) SE ×L SE…(8) (In mathematical expression (8), D) SE The density of the complex electrolyte (unit: g·cm³) -3 M SE The mass of the complex electrolyte (unit: g), S SE This indicates the contact area between the electrode and the composite electrolyte (unit: cm²). 2 ), L SE This indicates the thickness of the composite electrolyte (unit: cm). For the composite electrolyte HSE-1 obtained in Example 1, M SE =0.015, S SE =0.785, the density (D) obtained by the above mathematical formula (8) SE The value is 2.33 (g·cm). -3 ).
[0168] The density (D) of the composite electrolyte obtained above SE The porosity (φ) of the composite electrolyte HSE-1 obtained in Example 1 is calculated using the following mathematical formula (9). SE The result was 0%.
[0169] φ SE =(1-D SE / D′ SE )×100 …(9) (In mathematical expression (9), φ) SE D represents porosity (unit: %) SE The density of the complex electrolyte (unit: g·cm³) -3 ), D′ SE (This represents the theoretical density of the composite electrolyte.) It should be noted that the theoretical density D′ in the porosity measurement SE This is the sum of values obtained by multiplying the theoretical density of each solid electrolyte (inorganic solid electrolyte and organic solid electrolyte) by the mass ratio of each component. The theoretical density D′ of the composite electrolyte HSE-1 obtained in Example 1 is... SE It is 2.33 (unit: g·cm). -3 ).
[0170] [Examples 2-7, Comparative Examples 1-3] The types and amounts of raw materials, as well as the temperature in the heating process, were changed as described in Table 3. Otherwise, the same procedures as in Example 1 were performed to obtain composite electrolytes HSE-1 to HSE-10. Furthermore, the ionic conductivity (σ) of the obtained composite electrolytes HSE-1 to HSE-10 was measured using the same method as in Example 1. SE ) and porosity (φ)SE The results are shown in Table 3.
[0171] [Table 3]
[0172] Evaluation Results As shown in Table 3, the composite electrolytes of Examples 1-7, which were manufactured using molecular crystals as organic solid electrolytes and had a porosity of less than 15%, exhibited higher ionic conductivity than the composite electrolytes of Comparative Examples 1-3, which had a porosity exceeding 15%. The superior ionic conductivity of the composite electrolytes of Examples 1-7 is attributed to the fact that the molecular crystals, being organic solid electrolytes, filled the gaps between the inorganic solid electrolyte particles, thus creating ionic conduction pathways.
[0173] The results above show that composite electrolytes containing inorganic solid electrolytes and molecular crystals (organic solid electrolytes) with a porosity below a specified value exhibit high ionic conductivity.
[0174] This invention is not limited to the embodiments described above, and includes various modifications and variations within the same scope without departing from the spirit of the invention. Therefore, it should be understood that, in accordance with the above teachings, various combinations, forms, and other combinations and forms including only one element, its superordinate concept, or its subordinate concept also fall within the scope and spirit of this invention.
[0175] Explanation of reference numerals in the attached figures 10… Press mold.
Claims
1. A composite electrolyte, characterized by, containing an inorganic solid electrolyte and an organic solid electrolyte, the organic solid electrolyte contains a molecular crystal, the composite electrolyte has a porosity of 15% or less.
2. The composite electrolyte of claim 1, wherein, the inorganic solid electrolyte contains an oxide having a NASICON-type crystal structure.
3. The composite electrolyte of claim 2, wherein, The oxide having a NASICON-type crystal structure includes a general formula: Li 1+x+y-z M1 x Zr 2-x M2 y M3 z P 3-y-z O 12 The solid electrolyte is shown, wherein M1 includes Fe, In, or Al, M2 includes Si, M3 includes W, and x>0, y≥0, z≥0, and y+z>0 are satisfied.
4. The composite electrolyte of claim 2, wherein, The oxide having a NASICON-type crystal structure includes a general formula: Na 3+2x+y+α M4 x M5 y M6 z Zr 2-x-y-z Si 2+α P 1-α O 12 The solid electrolyte shown, wherein M4 includes an element that is a divalent cation, M5 includes Al, and includes or does not include an element other than Al that is a trivalent cation, M6 includes Ti, and includes or does not include an element other than Ti, Zr, and Si that is a tetravalent cation, satisfies x≥0, y≥0, z≥0, and x+y+z>0, and satisfies α>0.
5. The composite electrolyte of claim 1, wherein, the molecular crystal contains an organic molecule and an alkali metal salt as constituent units.
6. The composite electrolyte of claim 5, wherein, the organic molecule has a carbon atom number of 6 or less per 1 molecule.
7. The composite electrolyte of claim 5, wherein, the alkali metal salt contains an imide-based alkali metal salt.
8. The composite electrolyte of claim 5, wherein, the organic molecule has at least one atom selected from a sulfur atom, an oxygen atom, a nitrogen atom, and a phosphorus atom.
9. The composite electrolyte of claim 5, wherein, the organic molecule is at least one selected from a sulfone and a nitrile.
10. A power storage device characterized by comprising: a composite electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium-ion conductive composite material comprising at least one polymer and lithium-ion conductive particles
JP2022160569A
Laminate film
JP2023108816A